2015
DOI: 10.1016/s0140-6736(15)60127-1
|View full text |Cite|
|
Sign up to set email alerts
|

An internet-delivered handwashing intervention to modify influenza-like illness and respiratory infection transmission (PRIMIT): a primary care randomised trial

Abstract: Medical Research Council.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
163
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 114 publications
(170 citation statements)
references
References 27 publications
1
163
1
5
Order By: Relevance
“…PRIMIT (PRImary care trial of a website based Infection control intervention to Modify Influenza-like illness and respiratory infection Transmission) was a large randomised controlled trial (RCT) that showed a DBCI to be effective at lowering the transmission of colds, influenza and stomach upsets within the home through increased handwashing [25]. The framework was used to inform and structure the process of updating and amending the intervention ready for dissemination as an open-access resource for use by the general public.…”
Section: Applying the Framework During Development: Germ Defencementioning
confidence: 99%
“…PRIMIT (PRImary care trial of a website based Infection control intervention to Modify Influenza-like illness and respiratory infection Transmission) was a large randomised controlled trial (RCT) that showed a DBCI to be effective at lowering the transmission of colds, influenza and stomach upsets within the home through increased handwashing [25]. The framework was used to inform and structure the process of updating and amending the intervention ready for dissemination as an open-access resource for use by the general public.…”
Section: Applying the Framework During Development: Germ Defencementioning
confidence: 99%
“…This suggests that a decision-theoretic approach will be required (and may be sufficient by itself) in some circumstances, such as where the intervention could not conceivably cause harm, and where the likely effect size would produce an estimate of cost effectiveness that is well below currently acceptable thresholds. 19,20 For example, in a hand washing intervention designed for use in an influenza pandemic, 21 international dissemination of a fully automated digital intervention to reduce spread of respiratory infection would likely result in healthcare savings and wider health and socioeconomic benefits so great that the cost of the intervention becomes negligible.…”
Section: Medical Research Council Framework For Complex Interventionsmentioning
confidence: 99%
“…22 In similar fashion, the effectiveness and cost effectiveness of DHIs may depend on diffusion through social networks for uptake and effect. For example, an Internet-delivered hand washing intervention resulted in reductions in respiratory infection in the user and also in family members who had not engaged with the intervention directly, 21 and smaller effects could spread more widely. In addition, there may be feedback loops and potentially non-linear relationships, such as effectiveness at the individual level being partly dependent on nature of uptake at the group level (e.g.www.gettheworldmoving.com).…”
Section: Medical Research Council Framework For Complex Interventionsmentioning
confidence: 99%
“…While handwashing to the reduce spread of infection has always been advocated, there is now firm evidence that this does reduce spread of respiratory infections. 57 Advice on avoidance of other triggers is less clear-cut. 7 For example, UK asthma guidelines discuss the potentially paradoxical effects of removing a pet from the home: it may improve symptoms; however, removal of the allergen source also reduces the opportunity for tolerance developing, which itself may reduce symptoms.…”
Section: Lifestyle Advice and Triggersmentioning
confidence: 99%